2014
DOI: 10.1155/2014/437971
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence in Egypt: Results of the National Population-Based Cancer Registry Program

Abstract: Background. This paper aims to present cancer incidence rates at national and regional level of Egypt, based upon results of National Cancer Registry Program (NCRP). Methods. NCRP stratified Egypt into 3 geographical strata: lower, middle, and upper. One governorate represented each region. Abstractors collected data from medical records of cancer centers, national tertiary care institutions, Health Insurance Organization, Government-Subsidized Treatment Program, and death records. Data entry was online. Incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
529
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 711 publications
(555 citation statements)
references
References 19 publications
21
529
5
Order By: Relevance
“…[1,2] In Egypt, incidences of liver cancer have risen dramatically over the last two decades, and now it is the most common cancer in men and the second most common cancer in women, [3] with an annual rate of HCC development of 1-4%, when hepatitis C virus (HCV)-related cirrhosis is established. [1] Patients suffering from HCC unlike most solid tumors are confronted with the coexistence of two life-threatening conditions, malignancy and cirrhosis, which makes their prognostic assessments difficult.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] In Egypt, incidences of liver cancer have risen dramatically over the last two decades, and now it is the most common cancer in men and the second most common cancer in women, [3] with an annual rate of HCC development of 1-4%, when hepatitis C virus (HCV)-related cirrhosis is established. [1] Patients suffering from HCC unlike most solid tumors are confronted with the coexistence of two life-threatening conditions, malignancy and cirrhosis, which makes their prognostic assessments difficult.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in a study done in Egypt by Ibrahim et al, (4) who found that Upper Egypt represents the most prevalent incidence compared to lower & middle Egypt (38.7%, 33.2 % & 26.8 % respectively)these findings alarm the health care providers especially in Upper Egypt to increase women awareness toward breast cancer preventive measures through implementing an intervention educational program.…”
Section: Discussionmentioning
confidence: 79%
“…(1) According to World Health Organization 2010, there were about 519,000 women who die from breast cancer annually and about one million of women develop breast cancer each year. (2,3) The most recent study by Ibrahim et al (4) reported that cancer incidence rates based on national and regional level of Egypt revealed 157 per 100,000 among females. The commonest site was breast (32.0%) and the study added that by 2050, this incidence will be a 3-fold increase cancer relative to 2013 estimated rates.…”
Section: Introductionmentioning
confidence: 99%
“…As part of our ongoing program for developing anticancer agents based on a natural product scaffolds herein, we synthetized novel analogues of neocryptolepine compounds bearing sulfonyl-and carbonyl hydrazide moieties and evaluated their anticancer activity against the most common cancer in Egypt hepatocellular carcinoma (Ibrahim et al, 2014). …”
Section: Introductionmentioning
confidence: 99%